An Update on the Role of Immunohistochemistry in the Evaluation of Gastrointestinal Tract Disorders. (May 2020) - Robertson, Scott; Patil, Deepa T.
Abstract : As in other organ systems, immunohistochemistry (IHC) serves as an ancillary diagnostic tool for a wide variety of neoplastic and non-neoplastic disorders, including infections, work-up of inflammatory conditions, and subtyping neoplasms of the gastrointestinal (GI) tract. In addition, IHC is also used to detect a variety of prognostic and predictive molecular biomarkers for carcinomas of the GI tract. The purpose of this review is to highlight the use of IHC in common diagnostic scenarios throughout the tubular GI tract. The clinical indication and guidelines for performing IHC for detecting Helicobacter pylori is discussed along with role of gastrin and neuroendocrine markers in the diagnosis of autoimmune metaplastic atrophic gastritis. The major portion of this review discusses the use of IHC in the diagnostic workup of malignant neoplasms of the GI tract, such as adenocarcinoma versus squamous cell carcinoma, workup of poorly differentiated malignant neoplasms, and evaluation of uncommon gastric neoplasms (alpha-feto protein–producing carcinomas) and switch/sucrose-nonfermenting complex-deficient carcinomas. Lastly, localization of neuroendocrine tumors of unknown origin to aid clinical management, as well as HPV-driven anal neoplasia and IHC in the workup of basaloid anal neoplasms are also reviewed.